Final report on survey of packaging manufacturers and users in CARICOM (CARIRI TunapunaTT, 1992)
Examines the supply capacity and capability in the CARICOM Common Market. Looks at the process of production; the sources of inputs into production; and seeks to determine the market acceptability of the commodities.
DC